Prospective study of New Zealand infants with birth weight less than 1500 g and screened for retinopathy of prematurity: visual outcome at age 7–8 years. Issue 11 (1st November 1997) - Darlow, Brian A; Clemett, Richard S; Horwood, L John; Mogridge, Nina
Abstract : AIM: To determine the visual outcome at 7–8 years in very low birth weight (VLBW: birth weight <1500 g) infants screened for retinopathy of prematurity (ROP). METHODS: In 1986 all 413 VLBW infants admitted to neonatal units in New Zealand were enrolled in a prospective study of acute ROP. Surviving infants were traced and assessed at a home visit. Visual assessment comprised examination for abnormal and range of eye movements, visual fields, distance and near visual acuity, stereopsis, and photorefraction. RESULTS: Of 338 infants surviving to discharge, 313 (93%) had been examined for acute ROP. ROP was present in 66 (21%: ROP+), absent in 247 (ROP−), with 25 not examined (NA). 298 children (96% survivors resident in New Zealand: 91% all survivors) were assessed. Any visual problem occurred in 79% ROP+ and 60% ROP−/NA (p<0.01). Distance visual acuity less than 4/10 in the worse eye occurred in 29% ROP+ and 15% ROP−/NA (p<0.05); and in the better eye in 19% ROP+ and 5% ROP−/NA (p<0.001). Any myopia in the worse eye occurred in 36% ROP+ and 18% ROP−/NA (p<0.01); and in the better eye in 25% ROP+ and 11% ROP−/NA (p<0.01). Strabismus, including treated, occurred in 33% ROP+ and 19% ROP−/NA (p<0.05). Overall, 11% had astigmatism and 18% hypermetropia with no difference between the groups. CONCLUSION: In a population based study it was confirmed that VLBW is associated with an increased risk of visual problems at school age. A history of ROP is associated with an additional risk of poor outcome, including a near doubling of poor distance acuity, myopia, and strabismus.